2016
DOI: 10.1089/wound.2015.0670
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Nude Mouse Model of Hypertrophic Scarring Using Scratched Full Thickness Human Skin Grafts

Abstract: Objective: Hypertrophic scar (HTS) is a dermal form of fibroproliferative disorder that develops following deep skin injury. HTS can cause deformities, functional disabilities, and aesthetic disfigurements. The pathophysiology of HTS is not understood due to, in part, the lack of an ideal animal model. We hypothesize that human skin with deep dermal wounds grafted onto athymic nude mice will develop a scar similar to HTS. Our aim is to develop a representative animal model of human HTS. Approach: Thirty-six nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…Several studies have shown that grafting human skin onto an immunocompromised mouse leads to hypertrophic scarring 14,15,20 . Hypertrophic scarring, most often thought of as a dermal process, also receives input from the neighboring epidermis 27,28 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have shown that grafting human skin onto an immunocompromised mouse leads to hypertrophic scarring 14,15,20 . Hypertrophic scarring, most often thought of as a dermal process, also receives input from the neighboring epidermis 27,28 .…”
Section: Resultsmentioning
confidence: 99%
“…In this study we follow the gross and histologic changes in grafted human skin as it heals from an ischemic insult in a model of full thickness human skin wound healing, using the NBSGW mouse. While other investigators have described full thickness human skin healing on the athymic mouse, this model has been abandoned in favor of transplantation of partial thickness skin 6,14,20,30,31 . Partial thickness skin is often chosen over full thickness skin because it heals faster (generally within 7 weeks in our experience; unpublished data); the thinner dermal component revascularizes more rapidly, therefore, the model is ready for experimentation sooner than full thickness skin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In histology, we found reduced hair follicles and rete ridges, increased cells and blood vessels, thin collagen fiber accumulation parallel to the skin surface, elevated TGFβ and reduced decorin, and recruitment of macrophages, mast cells, fibrocytes and myofibroblasts. To confirm that human skin survives the wound healing process, black human skin was grafted onto mouse and black scar developed ( Figure 3D) [4][5][6]. Besides nude mice, scars also developed in RAG1, RAG2 and TCR knockout mice, in which mature T, B, NK cells and T cell receptors are deficient, suggesting that non-specific immune cells such as macrophages and mast cells may play a significant role in this dermal fibrotic model [7].…”
Section: Journal Of Aesthetic and Reconstructive Surgery Issn 2472-1905mentioning
confidence: 94%
“…The roles of non-specific immune cells in wound healing and scarring have being studied now. Based on this model, we further modified the mouse model by grafting full-thickness human skin with a deep wound, in which the deep wound was created using a jig before or after grafting, which may create a more promising dermal fibrotic mouse model ( Figure 4) [6].…”
Section: Journal Of Aesthetic and Reconstructive Surgery Issn 2472-1905mentioning
confidence: 99%